Prevention of Alcohol Consumption Programs for Children and Youth: A Narrative and Critical Review of Recent Publications - Sánchez-Puertas, Rafael; Vaca-Gallegos, Silvia; López-Núñez, Carla; Ruisoto, Pablo (Frontiers in Psychology, 2022)
Background: Youth substance use is a public health problem globally, where alcohol is one of the drugs most consumed by children, and youth prevention is the best intervention for drug abuse. Objective: Review the latest evidence of alcohol use prevention programs in empirical research, oriented to all fields of action among children and youth. Methods: A narrative and critical review was carried out within international databases (PsychInfo, Pubmed, Web of Science, and Scopus) in August 2021 and was limited to empirical studies that appeared in the last five years (2017-2021). A flow diagram was used according to the PRISMA statements. Empirical research articles in English with RCTs and quasi-experimental design that included alcohol, children, and young people up to 19 years of age (universal, selective, or indicated programs) were included. The authors examined the results and conceptual frameworks of the Prevention programs by fields of action. Results: Twenty-two articles were found from three fields of action: school (16), family (2), community (2), and web-based (2), representing 16 alcohol prevention programs. School-based alcohol prevention programs are clinically relevant (Theory of Planned Behavior, Refuse, Remove, Reasons, Preventure, The GOOD Life, Mantente REAL, Motivational Interviewing (BIMI), Primavera, Fresh Start, Bridges/Puentes), they are effective in increasing attitudes and intentions toward alcohol prevention behavior, while decreasing social norms and acceptance of alcohol, reducing intoxication, and increasing perceptions with regards to the negative consequences of drinking. Discussion: This narrative and critical review provides an updated synthesis of the evidence for prevention programs in the school, family, community, and web-based fields of action, where a more significant number of programs exist that are applied within schools and for which would have greater clinical relevance. However, the prevention programs utilized in the other fields of action require further investigation.